2017
DOI: 10.1021/acsami.7b00444
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Electrochemical Detection of Glycoprotein Based on Boronate Affinity Sandwich Assay and Signal Amplification with Functionalized SiO2@Au Nanocomposites

Abstract: Herein we propose a multiple signal amplification strategy designed for ultrasensitive electrochemical detection of glycoproteins. This approach introduces a new type of boronate-affinity sandwich assay (BASA), which was fabricated by using gold nanoparticles combined with reduced graphene oxide (AuNPs-GO) to modify sensing surface for accelerating electron transfer, the composite of molecularly imprinted polymer (MIP) including 4-vinylphenylboronic acid (VPBA) for specific capturing glycoproteins, and SiO nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 55 publications
0
37
0
1
Order By: Relevance
“…Boronate affinity-based molecular imprinting is a new, facile, and reliable approach for imprinting sugars, small biological molecules, ribonucleo- tides, and glycoproteins because of its unique reversible covalent binding of boronate with cis-diol compounds [124]. Ultrasensitive electrochemical strategy was proposed for detection of glycoprotein based on boronate affinity sandwich assay and signal amplification with functionalized SiO 2 @Au nanocomposites [125]. In this approach, the AuNPs-GO was immobilized on the glassy carbon electrode (GCE) surface using chitosan, conjugated with 4-mercaptophenylboronic acid (MPBA) to capture target glycoprotein, and then fabricate the MIP film.…”
Section: Electrochemical Mip Sensor For Detection Of Proteinmentioning
confidence: 99%
“…Boronate affinity-based molecular imprinting is a new, facile, and reliable approach for imprinting sugars, small biological molecules, ribonucleo- tides, and glycoproteins because of its unique reversible covalent binding of boronate with cis-diol compounds [124]. Ultrasensitive electrochemical strategy was proposed for detection of glycoprotein based on boronate affinity sandwich assay and signal amplification with functionalized SiO 2 @Au nanocomposites [125]. In this approach, the AuNPs-GO was immobilized on the glassy carbon electrode (GCE) surface using chitosan, conjugated with 4-mercaptophenylboronic acid (MPBA) to capture target glycoprotein, and then fabricate the MIP film.…”
Section: Electrochemical Mip Sensor For Detection Of Proteinmentioning
confidence: 99%
“…Protein glycosylation, a dynamic and ubiquitous protein posttranslational modifications, plays anextremely predominant role in numerous biological processes, including inter‐ and intracellular signal transduction, tumor immunology, cells migration, and protein folding [1‐2]. Moreover, research have shown that aberrant glycosylation is often accompanied by the occurrence of various physiological diseases, such as cancer, Alzheimer's cardiovascular disease, and Rheumatoid Arthritis [3‐5]. Hence, the specific analysis of glycoproteins is of great significance for the early diagnosis and real‐time monitoring of some diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A general and simple approach was proposed for the preparation of molecularly imprinted magnetic nanoparticles by using glycoproteins as the templates . Boronate affinity sandwich assay on functionalized SiO 2 @Au nanocomposites was used for ultrasensitive electrochemical detection of glycoproteins . A molecularly imprinted polymer was evaluated for pH and temperature controlled sensing of glycopeptide based antibiotics .…”
Section: Introducti̇onmentioning
confidence: 99%
“…The synthesis of molecularly imprinted sorbents by using boronate affinity interaction with the cis‐diol functionalized molecules has been usually performed by selecting nanoparticles as the supports . However, the imprinted nanoparticles are mostly suitable for the chromatographic applications performed based on biomagnetic separation conducted in batch fashion .…”
Section: Introducti̇onmentioning
confidence: 99%